2015
DOI: 10.1186/s40413-015-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, familial and environmental correlates of asthma among early adolescents in Sri Lanka: a case control study

Abstract: BackgroundDespite advances in management, the mortality and morbidity due to asthma are increasing globally. Identification of specific correlates in the local context is useful in disease management. The objective of this study was to estimate the prevalence and to describe selected correlates of asthma among12-14 year old school children in a district in Sri Lanka.MethodA school based cross-sectional study was conducted using a self administered questionnaire. Multi-staged stratified cluster sampling was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(28 reference statements)
1
14
1
Order By: Relevance
“…Regional differences in the dietary patterns, life styles, differences in survey methods, inclusion of different age groups, and changing diagnostic criteria would have contributed to these differences. The prevalence of asthma in this study is more than that previously reported by Danansuriya et al[21] (10.7%) in Sri Lankan adolescents aged 12-14 years. However, the prevalence rate of asthma reported in this study is within the range reported by the ISAAC studies carried out throughout the world, which ranged between 0.8% to 32.6% among adolescents aged 13 to 14 years[4].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Regional differences in the dietary patterns, life styles, differences in survey methods, inclusion of different age groups, and changing diagnostic criteria would have contributed to these differences. The prevalence of asthma in this study is more than that previously reported by Danansuriya et al[21] (10.7%) in Sri Lankan adolescents aged 12-14 years. However, the prevalence rate of asthma reported in this study is within the range reported by the ISAAC studies carried out throughout the world, which ranged between 0.8% to 32.6% among adolescents aged 13 to 14 years[4].…”
Section: Discussioncontrasting
confidence: 60%
“…Consent was obtained from the school administration, parents, and the children themselves. Previously translated and validated Rome III questionnaire (self-reported form for children above 10 years)[7,19] and International Study on Asthma and Allergies in Childhood (ISAAC) questionnaire[20,21] were used to diagnose FAPDs and asthma, respectively. HRQoL was evaluated using translated and pretested Pediatric Quality of Life Inventory 4.0 (PedsQL - Generic Core Scales) self-report form for teens[7,22].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, our study did not collect data on family history of allergic disorders. Previous study found that children with family history of allergy had a higher risk of asthma than those without family history 28 . Since family history of asthma isn’t related with CS, it may not confound the association between CS and the risks of childhood asthma and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 90%
“…The full scope of molecular mechanisms underpinning the changes seen in asthma is still unclear. Plausible contributory mechanisms include genetic predisposition [5][6][7][8][9], epigenetic alterations [10,11], exposure to environmental pollutants [12,13], chemicals [14] and viral infections [15] acting as triggers of inflammation.…”
mentioning
confidence: 99%